Healthcare utilization among people with disabilities in Iran: what predictors are associated with medical visits? - Fardin Moradi; Badriyeh Karami; Moslem Soofi; Behzad karamimatin; Faramarz Jalili; Shahram Akbari; Shahin Soltani (BMC Health Services Research)
Abstract Background Ensuring equitable access to healthcare services for individuals with disabilities poses a significant challenge for healthcare systems. This research aimed to explore the factors affecting medical visits among this population. Method This cross-sectional study in Iran involved data from 766 adults with disabilities aged 18 and older. Unadjusted and adjusted logistic regression analyses were used to calculate the odds ratios for medical visits. Results The majority of participants were male (64.36%) and single (54.02%). In the adjusted model, participants with severe disabilities (OR: 1.901, p = 0.025) were more likely to utilize medical visits compared to those with less severe disabilities. Conversely, individuals in the second (OR: 0.420, p = 0.017), fourth (OR: 0.360, p = 0.004), and fifth (OR: 0.319, p = 0.001) wealth quintiles demonstrated a significantly lower likelihood of accessing medical visits in comparison to the reference group. Conclusions This study reveals critical disparities in healthcare access for individuals with disabilities in Iran. While individuals with severe disabilities demonstrate a higher likelihood of utilizing medical services, those in lower wealth quintiles face significant barriers to accessing care. These findings emphasize the urgent need for targeted interventions to enhance healthcare equity, ensuring that financial constraints do not hinder medical visits for this vulnerable population.